Implementasi Fungsi Organisasi Melalui Kegiatan Pemetaan Kawasan Rawan Dan Rentan Narkoba Di Kota Bengkulu - Marlianto, Nuche; RS, Danur Azissah; Pebriani, Emi; Ramlis, Ravika; Hermiati, Dilfera (Universitas Dehasen Bengkulu, 2024)
Narcotics and psychotropic substances are drugs, materials that are useful in the field of health care, but on the other hand can cause dependence which is very detrimental if used without strict supervision. Narcotic substances were originally indicated for medicinal purposes, but with the development of science and technology, types of narcotics can be misused. Drug abuse has become a serious problem in various countries, both in developed countries and in Indonesia. To deal with the problem of narcotics, the activity